Recent Progress in Black‐Phosphorus‐Based Heterostructures for Device Applications. Issue 2 (27th November 2017) - Yang, Zhibin; Hao, Jianhua
Abstract: The rise of 2D layered materials has inspired luxuriant research interests in the development of novel nanodevices. Thanks to van der Waals interlayer forces and being free of dangling surface bonds, 2D materials are favorable for constructing vertical heterostructures by combining materials with different features. In recent years, ultrathin black phosphorus (BP) has been rediscovered as a new member of the 2D family and is attracting significant research attention due to its outstanding electronic properties and tunable bandgaps, which offers a new avenue for the creation of novel 2D heterostructures. Here, the recent development of heterostructured architectures based on 2D BP nanosheets is summarized with an emphasis on device characterizations. Stacks of phosphorene with graphene, semiconductors, or insulators are reviewed, along with methods to characterize the corresponding proof‐of‐concept devices, as well as potential opportunities for applications in the 2D limit, including transistors, optoelectronic devices, and sensors, with unprecedented functionalities. Finally, the challenges ahead of BP heterostructures are discussed and some future outlooks are suggested. Abstract : Black‐phosphorus van der Waals heterostructures are highlighted with a view to device demonstration. A variety of combinations of phosphorene and other materials with diverse functionalities are reviewed. The corresponding proof‐of‐concept applications of these heterostructures, including field‐effect transistors, sensors, and energy‐storage devices are discussed and summarized.